Land management, dynamics and vegetation vulnerability analysis in the Guna-Tana watershed as a predictor of land degradation, using remote sensing data - Mulualem Asfaw Ejegu; Kinda Gebyahu Reta; Endalkachew Sisay Yegizaw; Belay Zeleke Biru; Debrie Mersha Mekonnen; Gebrie Kassa Wassie; Melak Abebe Tegegne; Tiku Melak Dirar; Yosef Gebremikeal Dubale (Brawijaya University, 2022)
The vegetative coverage throughout the world is rapidly changing, which also directly affects the land degradation. Therefore, this study was intended to investigate the vegetation vulnerability analysis triggered by land use/land cover (LULC) dynamics as an indicator of land degradation conditions using Remote Sensing and GIS in Guna-tana watershed. Trend studies and cross-sectional research design was employed, which produces data from the population at a particular point in time and to examine patterns of change with a mixed research approach to examine the degree of influence to measure the sensitivity analysis. A multi-criteria decision evaluation was used to create a vegetation vulnerability map for the research area. The vulnerability model was run using four sets of parameters: closeness to the road, slope, settlement closeness, and land use planning. Landsat imageries of 1995 and 2020 was used to conduct a comparative study of land use pattern. The study area has experienced a sequence of land degradation from 1995 to 2020, according to the results of multitemporal data. Agricultural and built-up lands have increased throughout this time, while forest and shrub land has decreased. The vegetation vulnerability of the area also shows that 19.23% extreme vulnerable and 67.03% very strongly vulnerable which is more than 80% of the area is highly vulnerable to vegetation. Vegetation suitability and land management evaluation is critical for determining the risk of land deterioration, that shows the adverse effects on ecological elements due to a decrease in metabolic capacity and patch disintegration processes.